Etika Kristen dalam Menghadapi Krisis Moral Generasi Muda di Era Digital - Allen Jordi Ibrani (Coram Mundo: Jurnal Teologi dan Pendidikan Agama Kristen, 2025)
This study examines Christian ethics in responding to the moral crisis of young people in the digital era. The development of social media, algorithmic culture, and the attention economy has shaped how young people construct identity, manage desire, build relationships, and make moral decisions. The central issue explored in this study is not merely digital misconduct, such as hoaxes, cyberbullying, pornography, self-display culture, and social media addiction, but the fracture of Christian self-awareness that separates faith from everyday digital practices. This research employs a descriptive qualitative method through library research and theological-ethical analysis. The data were analyzed through thematic reduction, categorization of digital moral issues, and interpretation based on Christian ethical principles. The findings show that the digital moral crisis must be understood as a problem of identity, desire formation, and character development. Therefore, this study constructs a model of digital Christian ethics consisting of digital moral literacy, digital character discipline, digital discipleship community, and digital witness. The implication is that families, churches, and Christian educational institutions must develop systematic, contextual, and transformative digital ethics formation.